Hydrogen diffusivity and tensile-ductility loss of solution-treated austenitic stainless steels with external and internal hydrogen. (4th May 2017) - Yamabe, Junichiro; Takakuwa, Osamu; Matsunaga, Hisao; Itoga, Hisatake; Matsuoka, Saburo
Abstract: The effects of external and internal hydrogen on the slow-strain-rate tensile (SSRT) properties at room temperature were studied for ten types of solution-treated austenitic stainless steels containing a small amount of additive elements. The hydrogen diffusivity and solubility of the steels were measured with high-pressure hydrogen gas. The remarkable tensile-ductility loss observed in the SSRT tests was attributed to hydrogen-induced successive crack growth (HISCG) and was successfully quantified according to the nickel-equivalent content (Nieq ), which represents the stability of the austenitic phase. The relative reduction in area (RRA) of the steels with a larger Nieq was influenced by the hydrogen distribution, whereas that of the steels with a smaller Nieq was not. This unique trend was interpreted with regard to the hydrogen distribution and fracture morphology (HISCG or microvoid coalescence). Highlights: Austenitic stainless steels with a small amount of additive elements were tested. Effect of hydrogen on the slow-strain-rate tensile properties was studied. Hydrogen diffusivity and solubility were also determined. Tensile ductility loss was quantified according to the nickel-equivalent content. The ductility was interpreted from hydrogen distribution and fracture morphology.